A comparison of species diversity in two 1-ha plots at Tekai Tembeling Forest Reserve, Pahang, Malaysia - Eswani, Norhajar (Sciencedomain International, 2014)
Aims: The effects of commercial logging on tree species diversity in the Tekai Tembeling Forest Reserve (TTFR), Jerantut, Pahang is unknown. This article is focus on inventory of two forest plots having one ha area of each. Study Design: This study based on inventory conducted within the forest area. Place and Duration of Study: Tekai Tembeling Forest Reserve (TTFR), Pahang, Malaysia between 2008 and 2010. Methodology: 100 quadrats of 10mx10m were established in each plot. Hundred percent inventory was applied to collect the data which were analyzed using Ecological Methodology Software to calculate species diversity, richness and composition. Accordingly, species richness, species composition, evenness and species dominance were compared between two plots. Results: Altogether 34226 individuals were found in both plots which were belonging to 950 species under 321 genera and 107 plant families. Remarkably, 700 species were found in plot 2 while it was only 520 in plot 1. However, plot 1 comprised more stems than plot 2. The importance value index (IVI) value was found to be highest for Shorea curtisii among species group in plot 1 but in case of plot 2 it was highest for Knema hookeriana. So it can be concluded that these species were dominant species. In this study, individuals was all of the plants collected during inventory including trees, shrub, climbers, palm and so on while stand density only represent the number of plant with dbh at least 5cm. Total stand density and basal area were 1310 plants ha-1 and 27.52 m2 ha-1 respectively in plot 1 while they were 316 plants ha-1 and 9.50m2 ha-1 respectively in plot 2. Notably, Euphorbiaceae was the most diverse which was followed by Dipterocarpaceae plant family in both plots. Conclusions: Species diversity in Plot 2 was more diverse compared to Plot 1. However Plot 1 was more dense than Plot 2 with 18752 individual trees compared to 15459 in Plot 2.